INCLUSIVE EDUCATION STRATEGIES FOR CHILDREN WITH SENSORY DISABILITIES AND CONDITIONS FOR THEIR IMPLEMENTATION - A.T.Yo'ldoshov; S.T.Normurodova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article extensively discusses the relevance of inclusive education in the integration of children with sensory disabilities into the general education system, educational strategies, as well as the conditions necessary for their implementation. Individual approaches that meet the personal needs of each child, pedagogical methods, technological support, and the creation of a psychological environment are analyzed.